2016
DOI: 10.1016/j.tcm.2016.02.004
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA: A new therapeutic strategy for cardiovascular diseases

Abstract: Myocardial infarction, atherosclerosis and hypertension are the most common heart-related diseases that affect both the heart and the blood vessels. Multiple independent risk factors have been shown to be responsible for cardiovascular diseases. The combination of a healthy diet, exercise and smoking cessation keeps these risk factors in check and helps maintain homeostasis. The dynamic monolayer endothelial cell integrity and cell-cell communication are the fundamental mechanisms in maintaining homeostasis. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(56 citation statements)
references
References 105 publications
(120 reference statements)
1
53
0
2
Order By: Relevance
“…miRNA treatment options focus on the specific artificial elevation or suppression of selected miRNA levels. Detailed explanations on the mode of function of the diverse approaches on how to alter miRNA levels can be found elsewhere [17,135,136]. Briefly, a specific elevation of target miRNAs can be achieved by miRmimics [137], while miRNA suppression can be obtained by anti-miRNA antisense oligomers -so-called antagomiRs [138,139], sponges [140][141][142], masking [143] and erasers [139].…”
Section: Mirnas -Therapeutic Applicationmentioning
confidence: 99%
“…miRNA treatment options focus on the specific artificial elevation or suppression of selected miRNA levels. Detailed explanations on the mode of function of the diverse approaches on how to alter miRNA levels can be found elsewhere [17,135,136]. Briefly, a specific elevation of target miRNAs can be achieved by miRmimics [137], while miRNA suppression can be obtained by anti-miRNA antisense oligomers -so-called antagomiRs [138,139], sponges [140][141][142], masking [143] and erasers [139].…”
Section: Mirnas -Therapeutic Applicationmentioning
confidence: 99%
“…Many miRNA profiling studies in plasma or extracellular carriers have found significantly altered miRNAs in a wide-variety of diseases, many of which are now being considered as potential biomarkers for different aspects of CVD, see reviews (Joladarashi, Thandavarayan, Babu, & Krishnamurthy, 2014; Samanta, et al, 2016). At the time of this review, there are currently 159 clinical trials investigating miRNA biomarkers in diseases, including breast cancer (ClinicalTrials.gov identifier: NCT01612871), acute myeloid leukemia (NCT01057199), and periodontal disease (NCT02069574).…”
Section: Current Development Of Mirna Therapeutics That May Impactmentioning
confidence: 99%
“…The expression pattern of miRNAs can provide information about the pathophysiological processes underlying HF, such as myocardial fibrosis and hypertrophy [5, 15, 16]. For example, Duisters et al [17] showed that both miR-133 and miR-30 directly downregulate connective tissue growth factor, which is associated with myocardial fibrosis [8, 17].…”
Section: Discussionmentioning
confidence: 99%